Desenvolvimento do cuidado em saúde mental no contexto de consolidação da reforma psiquiátrica: a experiência de um CAPS em Santos - Wagner, Natália Cyrillo [UNIFESP] (2017)
By the end of the 1980s, with the creation of the Unified Health System (SUS), the first initiatives to replace mental asylums in Brazil took place. The city of Santos pioneered the process of creating the first network of territorial services for mental health. In this sense, within a process of paradigm change, it was expected that daily work routine presented difficulties and potentialities in the development and implementation of the psychosocial care model. It is also believed that the way of reflection of the practice makes possible the implementation of care actions wich contributes to overcome the challenges encountered, allowing the expansion of citizenship exercise, autonomy development and improvement of life quality of the users served, at the same time finding more effective ways to share these experiences among professionals and among the Psychosocial Care Network services. The aim of this research was to investigate the professionals' perception about their practice, organized by the understanding, construction and use of the Singular Therapeutic Project (PTS) as a strategy to direct care. Through the qualitative approach, a case study was carried out in a Psychosocial Care Center. The aim was to identify in this service, through semi-structured interviews applied to team professionals, the promotion of the changes advocated by the Movement of Anti-Asylum and Psychiatric Reform. Thus, a cut was used as a strategies organization resources used by care team, which consists of the Singular Therapeutic Project, the product of this mobilization process. The set of data produced was explored from the perspective of the Thematic Content Analysis. In the experience was a dynamic process composed of multiple understandings and several ways to deal in practice with the Singular Therapeutic Projects question. Finally, it was verified the importance of efforts aimed at the training of health workers, while valuing the prior knowledge of these professionals, as a strategy to strengthen practice, in an attempt to produce transformations not only within the services, but also in all social contexts where psychic suffering is produced and lived. Nevertheless, it is known that the training processes do not solve all the questions, but they can foment the learning that occurs in the daily practice.